THE UTILIZATION OF RIVERBANK AREAS AS TOURIST DESTINATIONS IN BANJARMASIN CITY - Jumriani, Jumriani; Arisanty, Deasy; Angriani, Parida (International Conference On Social Science Education, 2024)
This article explores the potential for developing riverbank areas in Banjarmasin City into tourist destinations through a comprehensive literature review. Banjarmasin, known as the "City of a Thousand Rivers," holds a unique geographical and cultural position that makes its riverbanks valuable for tourism. The study investigates various aspects of riverbank tourism, focusing on the benefits and challenges associated with utilizing these areas for economic development and cultural preservation. The literature analysis reveals that riverbank tourism can significantly boost local economies by attracting visitors while providing opportunities to showcase the city’s cultural heritage. However, challenges such as environmental degradation, inadequate infrastructure, and lack of community involvement present potential obstacles to sustainable development. The study emphasizes the need for a balanced approach that integrates tourism with environmental management and community participation. By synthesizing previous research, this paper provides insights into strategies for promoting sustainable riverbank tourism in Banjarmasin, contributing to the broader discourse on urban river tourism and development.